2014
DOI: 10.1111/1750-3841.12477
|View full text |Cite
|
Sign up to set email alerts
|

Shiga‐Toxin Genes and Genetic Diversity of Escherichia coli Isolated from Pasteurized Cow Milk in Brazil

Abstract: Knowledge about the presence of diarrheagenic Escherichia coli in pasteurized milk is important developing and implementing control measures in milk and dairy production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…These findings strongly suggest that these strains are the ones predominantly circulating in Danish farms and might be the archetypal commensal E. coli in the gut of pigs. Even though some isolates were predominant, and a limited number of profiles were found at the single animal level, we observed a high genetic diversity among E. coli strains isolated from different pigs regardless of whether they shared the same pen or not as previously demonstrated in other hosts [16, 2628]. We also showed that apparently the majority of profiles were represented by strains that are resistant to either ampicillin or tetracycline or both.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These findings strongly suggest that these strains are the ones predominantly circulating in Danish farms and might be the archetypal commensal E. coli in the gut of pigs. Even though some isolates were predominant, and a limited number of profiles were found at the single animal level, we observed a high genetic diversity among E. coli strains isolated from different pigs regardless of whether they shared the same pen or not as previously demonstrated in other hosts [16, 2628]. We also showed that apparently the majority of profiles were represented by strains that are resistant to either ampicillin or tetracycline or both.…”
Section: Discussionsupporting
confidence: 76%
“…While this limited number of different strains was observed at the animal level, REP-PCR DNA fingerprint analysis revealed extensive genetic diversity among E. coli strains isolated from different pigs regardless of whether they shared the same pen or not. The high genetic diversity displayed by E. coli was also demonstrated in humans and other animals such as cows, coyotes, sheep and goats in previous studies [16, 2628]. …”
Section: Discussionmentioning
confidence: 56%
“…The absence of non-D157 STEC isolates from cheeses collected in the others periods was a good indication of the involvement of the abovementioned food worker with the contamination process. Hoffmann et al (2014) analyzed 87 E. coli strains isolated from pasteurized milk obtained from 22 farm dairies located at Parana state in Brazil and did not detect the stx1, stx2, and eae virulence genes among the E. coli isolates. Dkura & Marin (2014) examined 330 E. coli strains isolated from 111 Minas frescal cheeses from Southwest Minas Gerais State and also did not detect stx 1, stx 2, or eae genes among the E. coli isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Wide ranges of genetic diversity were also demonstrated by others in studies on diversity of commensal E . coli from humans and from other animals [15,2729]. …”
Section: Discussionmentioning
confidence: 99%